Clinical and laboratory parameters associated with metabolic syndrome in Turkish patients with psoriasis. (April 2014) - Akcali, Cenk; Buyukcelik, Burcin; Kirtak, Necmettin; İnaloz, Serhat
Objectives: To assess clinical and laboratory parameters associated with metabolic syndrome in Turkish patients with moderate or severe plaque-type psoriasis and nonpsoriatic controls. Methods: Patients with moderate or severe plaque psoriasis (patient group) or with nonpsoriatic dermatological disease (controls) were included. Waist circumference, weight, height and arterial blood pressure were measured, together with fasting blood glucose, triglyceride, high density lipoprotein (HDL), fibrinogen, homocysteine and adiponectin levels. Metabolic syndrome was diagnosed using National Cholesterol Education Program–Adult Treatment Panel III criteria. Results: Out of 90 patients (50 with psoriasis; 40 controls), metabolic syndrome was more frequent in the patient group than in controls. In terms of metabolic syndrome parameters, only hypertension was more frequent in patients with psoriasis compared with controls. There was no statistically significant difference between the patient and control groups for obesity, hypertriglyceridaemia, HDL levels or hyperglycaemia. Fibrinogen levels were increased and adiponectin levels were decreased in the psoriasis group. No between-group difference in homocysteine levels was found. Conclusion: In this small study, metabolic syndrome was found to be more frequently identified in Turkish patients with psoriasis than in controls; metabolic syndrome could lead to increased cardiovascular disease risk in patients with moderate to severe psoriasis.